Carbohydrate-based approach for the total synthesis of strictifolione - Ramana, C. V.; Raghupathi, N.; Gurjar, M. K.; Chorghade, Mukund S. (Tetrahedron Letters, 2005)
A chiral pool approach starting with D-glucose, using the Yamaguchi protocol and a Z-selective HWE reaction followed by lactonization, has been applied to execute the total synthesis of strictifolione. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: D-Glucose; double elimination; Horner-Wadsworth-Emmons reaction; lactonization; strictifolione; Yamaguchi protocol

Ring-closing metathesis mediated total synthesis of microcarpalide and herbarumin III - Gurjar, M. K.; Nagaprasad, R.; Ramana, C. V.; Karmakar, S.; Mohapatra, Debendra K. (Arkivoc, 2005)
Total synthesis of naturally occurring microcarpalide and herbarumin III are described. The ring-closing metathesis (RCM) approach to coin the medium sized rings present in their molecular structures form the basic premise of this investigation.
Keywords: herbarumin III; microcarpalide; microfilament; phosphodiesterase; ring-closing metathesis (RCM)

Synthesis of eupomatilone-6 and assignment of its absolute configuration - Gurjar, Mukund K.; Karumudi, Bhargava; Ramana, C. V. (Journal of Organic Chemistry, 2005)
[GRAPHICS] The Zn-mediated Barbier reaction of the biarylaldehyde 8 with crotyl bromide followed by hydroboration and oxidation provided the gamma-butyrolactones 4 and 5. The stereoselective installation of methyl group at C-3 by using LiHMDS and MeI completed the synthesis of racemic eupomatilone-6 (2) and its diastereomer 3. The spectroscopic data of 2 was in fall agreement with reported spectra of natural product, thus confirming the revised relative configuration of eupomatilone-6. Similarly, an optically active (3R,4R,5S)-isomer of eupomatilone-6 (23) was prepared in which the aldol reaction with thiazolidinethione as a chiral auxiliary was employed as a key step. On the basis of the spectroscopic data and optical rotation values of 23, the absolute configuration of eupomatilone-6 was proposed.

Palladium mediated cycloisomerization of sugar alkynols: synthesis of cyclic enol-ethers and spiroketals - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Functionalized bicyclic enol-ethers and spiroketals are prepared by Pd catalyzed cycloisomerization of 3-C-alkynylfuranosyl derivatives. Cycloisomerization of differently substituted alkyne derivatives revealed a preference for 6-endo-dig cyclization over 5-exo-dig if the substituent is not sufficiently electron withdrawing. The scope of these cycloisomerizations has been further extended by integrating with conjugate addition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: c-alkynylfuranose; cycloisomerization; enol-ether; Palladium; Spiroketal

Pictet-Spengler cyclization in room temperature ionic liquid: a convenient access to tetrahydro beta-carbolines - Muthukrishnan, Murugan; More, Shivaji V.; Garud, Dinesh R.; Ramana, C. V.; Joshi, Rohini R.; Joshi, Ramesh A. (Journal of Heterocyclic Chemistry, 2006)
1,2,3,4-Tetrahydro-beta-carbolines have been synthesized in moderate to good yields in short reaction time using the ionic liquid [bbim] BF4 as reaction medium and promoter. There was no need for the use of an additional catalyst normally employed in Pictet-Spengler condensation.

Synthetic studies toward macrocidins: an RCM approach for the construction of the central cyclic core - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The central macrocyclic core of the macrocidins was constructed using RCM as the key reaction. A preliminary investigation dealing with the key reactions, that is, the Dieckmann cyclization and the RCM, revealed that RCM of the beta-ketoamide is better than RCM of the corresponding acyltetramic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: acyltetramic acid; Lacey-Dieckmann cyclization; macrocidins; Ring closing metathesis

Total synthesis of (-)-radicamine B - Gurjar, Mukund K.; Borhade, Ramdas G.; Puranik, Vedavati G.; Ramana, C. V. (Tetrahedron Letters, 2006)
The synthesis of a chiral cyclic nitrone with L-arabino configuration and its application in the total synthesis of radicamine B is reported. An agreement in the spectral data with natural radicamine B but specific rotation with an opposite sign warranted a revision of the absolute configuration of radicamine B. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: codonopsinine; Cyclic nitrone; Grignard addition; polyhydroxy pyrrolidine alkaloids; radicamine B

Carbohydrate based approach towards the synthesis of aspercyclide C - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A formal total synthesis of aspercyclide C (3) is described in which D-ribose is employed as a chiral pool material. The key step is a ring closing metathesis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: chiron approach; D-ribose; Mukaiyama reagent; ring closing metathesis (RCM); Ullmann coupling

Central core of uprolides D and E: a survey of some ring closing metathesis approaches - Ramana, C. V.; Salian, Sumanth R.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A preliminary study dealing with the feasibility of ring closing metathesis and ene-yne ring closing metathesis to construct the central bicyclic cores of uprolides D and E was investigated. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cembranolides; ene-yne metathesis; Ring closing metathesis; Sharpless asymmetric epoxidation; uprolides D and E

Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Synthesis of L-ido-configured six- and seven-membered carba-sugars - Ramana, C. V.; Chaudhuri, Siddhartha Ray; Gurjar, Mukund K. (Synthesis-Stuttgart, 2007)
Ring-closing olefin metathesis has been successfully applied to the modular construction of L-ido-configured six- and seven-membered carba-sugars.
Keywords: allylations; carbocycles; carbohydrates; Metathesis; Radical reactions

Total synthesis of pachastrissamine (jaspine B) enantiomers from D-glucose - Ramana, C. V.; Giri, Awadut G.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Synthesis of both enantiomers of pachastrissamine is described from a common chiral template. The stereoselective construction of the central tetrahydrofuran units was based on the pseudodesymmetrization of a pentodialdo-1,4-furanose derivative taking advantage of the latent symmetry present. (c) 2006 Published by Elsevier Ltd.
Keywords: 4-furanose; chiron approach; Ohira-Bestmann reaction; pachastrissamine/jaspine B; pentodialdo-1; ring isomerization

[2+2+2]-cyclotrimerization approach for the synthesis of enantiopure isochromans using a carbohydrate derived dialkyne template - Ramana, C. V.; Suryawanshi, Sharad B. (Tetrahedron Letters, 2008)
An easy access to enantiopure isochromans through cross alkyne trimerization of a glucose derived dialkyne was developed. One of the synthesized isochromans was converted into a novel tricyclic nucleoside by simple transformations. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: isochroman; tricyclic nucleoside; Vorbruggen reaction; Wilkinson's catalyst; [2+2+2]-Cyclotrimerization

Carbohydrate-based approach for the total synthesis of aculeatin D and 6-epi-aculeatin D - Ramana, C. V.; Srinivas, Burgula (Journal of Organic Chemistry, 2008)
A concise approach for the total synthesis of aculeatin D and 6-epi-aculeatin D employing differentially protected anti,anti-1,3,5-triol alkyne prepared from alpha-D-glucoheptonic-gamma-lactone derivative is documented. Phenol protecting group manipulation for selective O-debenzylation during the hydrogenation of the diyne intermediate and one-pot phenolic oxidation with concomitant spiroketalization highlight the accomplished total synthesis.

C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles

Expeditious one-step entry to the tetracyclic core of integrastatins - Ramana, C. V.; Reddy, Challa Nageswara; Gonnade, Rajesh G. (Chemical Communications, 2008)
Herein we describe a one-step assembly of structurally complex small molecules representing the central skeleton of integrastatins by employing a simple pinacol transform.

In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid

Influence of electronic factors on palladium-mediated cycloisomerization: a systematic investigation of competitive 5-exo-dig versus 6-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron, 2008)
Pd-mediated cycloisomerization of 3-C-alkynyl-allo- and ribofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity in ring closure reaction. The reactions in general are influenced by the electronic nature of the substituent on the alkyne unit. A preference for endo-dig cyclization over exo-dig is noted, if the alkynyl substituent is not sufficiently electron withdrawing, (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: C-alkynyl furanose; cycloisomerization; enol ether; Palladium; Spiroketal

Stereoselective synthesis of beta-C-Allyl- and beta-C-propargyl-D-arabinofuranosides - Ramana, C. V.; Narute, Sachin B.; Gonnade, Rajesh G.; Patil, Rahul S. (Synthesis-Stuttgart, 2008)
The stereoselective synthesis of beta-configured C-allyl- and C-propargyl-D-arabinofuranosides (4,7-anhydro-1,2,3-deoxy-D-gluco-oct-1-enitols and -oct-1-ynitols) was addressed by employing allylation/propargylation of a dialdofuranose under aqueous Barbier reaction conditions and acid-catalyzed furan ring transposition of 5-O-mesyl-manno-oct-7-eno- or 5-O-mesyl-manno-oct-7-ynofuranoside derivatives.
Keywords: Allylation; Barbier reaction; C-glycoside; D-mannose; propargylation; Ring transposition

Total synthesis and determination of relative and absolute configuration of multiplolide A - Ramana, C. V.; Khaladkar, Tushar P.; Chatterjee, Soumitra; Gurjar, Mukund K. (Journal of Organic Chemistry, 2008)
A flexible approach for total syntheses of possible multiplolide A diastereomers establishing the relative and absolute configuration is documented. The adopted strategy features ring-closing metathesis (RCM) as the key reaction and screening of a set of substrates for the feasibility of RCM in general and for the requisite E-configuration of ring olefin in particular. Selective protecting groups manipulation prior to the assembly of the central macrocyclic core was instrumental in installing the epoxide functionality on a fully deprotected nonenolide at the end of the synthesis.

Click synthesis of isomeric compounds for assessing the efficiency of the bifurcated Br center dot center dot center dot NO2 synthon - Ramana, C. V.; Chatterjee, Soumitra; Durugkar, Kulbhushan A.; Gonnade, Rajesh G. (Crystengcomm, 2009)
We report herein the extention of the azide-alkyne ``click reaction'' to crystal engineering and synthesize a collection of isomeric compounds with modular positioning of Br and NO2 on a tricyclic template and crystal structural analyses of the derived isomers. It is quite remarkable to notice that none of the isomers displayed the bifurcated three-center NO2 center dot center dot center dot Br supramolecular synthon in their crystal structures

Cu(I)-promoted one-pot `SNAr-click reaction' of fluoronitrobenzenes - Durugkar, Kulbhushan A.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2009)
A one-pot two-step sequence involving a nucleophilic aromatic substitution (SNAF) of activated fluorobenzenes with azide nucleophile and in situ Huisgen cycloaddition of the resulting aryl azides with alkynes has been developed for a rapid access to 1,4-substituted triazoles. Control experiments revealed that both the steps are catalyzed by Cu(I) and also the course of reaction as SNAr followed by [3+2]-cycloaddition. (C) 2009 Elsevier Ltd. All rights reserved.

Direct method for the preparation of glycolipid-metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity - Singh, Sanjay; Patel, Pitamber; Jaiswal, Swarna; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2009)
The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necessity for exogenous reducing agent and imparting better stability to the silver nanoparticles as compared to their oleic acid capped analogues. These sophorolipid capped silver nanoparticles can be obtained as a stable powder that can be re-dispersed in water as desired.

Formal synthesis of (+)-didemniserinolipid B employing a Pd-mediated 6-endo selective alkynediol cycloisomerization - Ramana, C. V.; Induvadana, Boddeti (Tetrahedron Letters, 2009)
Herein, we describe a concise assembly of central 6,8-dioxabicyclo[3,2,1]octane core of didemniserino-lipid by employing a Pd-mediated alkynediol cycloisomerization and a formal total synthesis of didemniserinolipid (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Didemniserinolipid; Yamaguchi oxirane alkyne coupling; Zipper reaction

Influence of electronic factors on pd-mediated cycloisomerization: a systematic investigation of competitive 6-exo-dig versus 7-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Induvadana, Boddeti; Srinivas, Burgula; Yadagiri, Kommagalla; Deshmukh, Madhusudhan N.; Gonnade, Rajesh G. (Tetrahedron, 2009)
Pd-mediated cycloisomerization of 3-C-propargyl-ribo- and allofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity (6-exo- vs 7-endo) of alkynol cycloisomerization leading either to a six- or seven-membered ring. In general, the 6-exo-dig mode of cyclization is facile and is independent of electronic factors. With some of the alkynols, a regioselective (7-endo?) hydration of the alkyne unit was observed and this has been attributed to the participation of C(3)-OH. When the C(3)-OH was protected as its benzyl ether, cycloisomerization of these alkynols occurred exclusively in a 6-exo-dig mode resulting in the corresponding [3.2.1]-bicyclic ketals. Additional control experiments conducted were in support of the participation of C(3)-OH in regioselective alkyne hydration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Palladium; Sonogashira coupling; Sugar alkynol

Pd(II)-mediated alkynediol spiroketalization: first total synthesis of (-)-cephalosporolide E and (+)-cephalosporolide F - Ramana, C. V.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2009)
Herein we describe a concise assembly of the central 1.6-dioxaspiro[4.4]nonane core of cephalosporolides E/F by employing a Pd-mediated alkynediol cycloisomerization and their total synthesis. On the basis of spectroscopic data and optical rotation values, the absolute configurations of cephalosporolides E/F were proposed.

Pd-mediated intramolecular ketalization of alkynediols: construction of the central [3.2.1]-bicyclic ketal core of cyclodidemniserinol trisulfate - Ramana, C. V.; Mallik, Rosy; Sahoo, Gokarneswar (Tetrahedron Letters, 2009)
A preliminary study dealing with the Pd-mediated alkynediol cycloisomerization to construct the central bicyclic ketal core of cyclodidemniserinol trisulfate is documented. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Cyclodidemniserinol trisulfate; Yamaguchi oxirane-alkyne coupling

Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

[Cu]-Catalyzed S(N)AR reactions: direct amination of electron deficient aryl halides with sodium azide and the synthesis of arylthioethers under Cu(II)-ascorbate redox system - Goriya, Yogesh; Ramana, C. V. (Tetrahedron, 2010)
A one pot [Cu]-promoted SNAr reaction of electron-deficient halobenzenes with sodium azide and the reduction of the intermediate aryl azides under the same Cu(II) ascorbate redox conditions leading to anilines has been documented. Control experiments revealed that both ascorbate and proline play important role in the reaction path way. Further, the use of this catalytic Cu(II) ascorbate redox system has been explored for the synthesis of arylthioethers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anilines; Azide reduction; Cu(II)-ascorbate redox system; SNAr reaction; Thioether

Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.

Isochroman- and 1,3-dihydroisobenzofuran-annulation on carbohydrate templates via [2+2+2]-cyclotrimerization and synthesis of some tricyclic nucleosides - Suryawanshi, Sharad B.; Dushing, Mangesh P.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2010)
The synthesis of enantiopure tricyclic systems comprising isochroman or dihydroisobenzofuran units integrated with sugar templates has been documented. The alkyne cylotrimerization reaction has been employed with easily accessible sugar diynes for the key bicyclic ring construction and thus a provision to alter the functional groups on the newly formed aromatic rings. By selecting two representative trimerization products, we have synthesized the tricyclic nucleosides by simple synthetic manipulations. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Dihydroisobenzofuran; Dihydroisobenzopyran; Modified nucleosides; Vorbruggen reaction; [2+2+2] cyclotrimerization

Modular total synthesis of aculeatins A, B, E, F and 6-epi-aculeatins E, F - Ramana, C. V.; Pandey, Sunil Kumar (Tetrahedron, 2010)
The total synthesis of aculeatins A, B. E and F confirming the assigned absolute configuration of recently isolated aculeatins E and F is documented. A convergent approach has been designed by the addition of both the terminal units (phenol and side chain) at an advanced stage. The central 1,3,5-triol unit with the requisite stereochemistry was prepared from the commercially available alpha-D-glucoheptonic-gamma-lactone. Selective O-debenzylation during the hydrogenolysis of the diyne intermediate and the one pot phenolic oxidation with concomitant spiroketalization highlight the accomplished total syntheses. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: aculeatins; Alkyne-oxirane coupling; Natural products synthesis; Oxidative spiroketalization; Sonogashira coupling

Small molecule inhibition of phosphatidylinositol-3,4,5-triphosphate (PIP3) binding to pleckstrin homology domains - Miao, Benchun; Skidan, Igor; Yang, Jinsheng; Lugovskoy, Alexey; Reibarkh, Mikhail; Long, Kai; Brazell, Tres; Durugkar, Kulbhushan A.; Maki, Jenny; Ramana, C. V.; Schaffhausen, Brian; Wagner, Gerhard; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The PI3-kinase (PI3K) pathway regulates many cellular processes, especially cell metabolism, cell survival, and apoptosis. Phosphatidylinositol-3,4,5-trisphosphate (PIP3), the product of PI3K activity and a key signaling molecule, acts by recruiting pleckstrin-homology (PH) domain-containing proteins to cell membranes. Here, we describe a new structural class of nonphosphoinositide small molecule antagonists (PITenins, PITs) of PIP3-PH domain interactions (IC50 ranges from 13.4 to 31 mu M in PIP3/Akt PH domain binding assay). PITs inhibit interactions of a number of PIP3-binding PH domains, including those of Akt and PDK1, without affecting several PIP2-selective PH domains. As a result, PITs suppress the PI3K-PDK1-Akt pathway and trigger metabolic stress and apoptosis. A PIT-1 analog displayed significant antitumor activity in vivo, including inhibition of tumor growth and induction of apoptosis. Overall, our studies demonstrate the feasibility of developing specific small molecule antagonists of PIP3 signaling.
Keywords: Anticancer; PIP3 antagonist

Target cum flexibility: an alkyne [2+2+2]-cyclotrimerization strategy for synthesis of trinem library - Ramana, C. V.; Dushing, Mangesh P.; Mohapatra, Sradhanjali; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron Letters, 2011)
A rapid access to the central 4,5,6-tricyclic core of 4,5,6-trinems has been achieved by employing the alkyne [2+2+2]-cyclotrimerization as the key and final reaction in the synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Target cum flexibility: synthesis of C(3 `)-spiroannulated nucleosides - Dushing, Mangesh P.; Ramana, C. V. (Tetrahedron Letters, 2011)
We report a simple strategy for the synthesis of a collection of C(3')-spirodihydroisobenzo-furannulated nucleosides featuring a [2+2+2]-cyclotrimerization as the key reaction. The cyclotrimerization reactions are facile with the unprotected nucleosides having a diyne unit. When both alkynes of the diyne are terminal, the regioselectivity is poor. However, when one of the terminal alkynes is additionally substituted, the cyclotrimerizations are highly diastereoselective. Since the key bicycloannulation is the final step, this strategy provides flexibility in terms of the alkynes and is thus amenable for the synthesis of a focussed small molecule library. (C) 2011 Published by Elsevier Ltd.
Keywords: Dihydroisobenzofuran; Modified nucleosides; Tanaka catalyst; Willkinson catalyst; [2+2+2]-Cyclotrimerization

Totall synthesis of (+/-)-sacidumllignan D - Pandey, Sunil Kumar; Ramana, C. V. (Journal of Organic Chemistry, 2011)
The first total synthesis of (+/-)-sacidumlignan D featuring a Zn-mediated Barbier reaction and reverse Wacker oxidation to form the key gamma-lactone, its diastereoselective alpha-methylation followed by reduction cyclization, was documented.

Stereospecific synthesis of C-arabinofuranosides and carba-disaccharide analogues of Motif C of cell wall AG complex of Mtb - Patil, Rahul S.; Ahire, Ketan M.; Ramana, C. V. (Tetrahedron Letters, 2012)
A simple strategy for the synthesis of alpha- and beta-C-arabinofuranosides featuring a furan ring transposition reaction has been developed. A novel double furan ring transposition reaction has proposed and executed for the synthesis of the carba-disaccharide analogue of Motif C of the cell wall AG complex of Mtb. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arabinose; C-Glycosides; Carba-disaccharide; Cell wall AG complex; Ring transposition

Total synthesis of (-)-isatisine A - Patel, Pitambar; Ramana, C. V. (Journal of Organic Chemistry, 2012)
A modular total synthesis of (-)-isatisine A is described in which four consecutive metal-mediated transformations have been employed at the final stage. These include [Pd]-catalyzed Sonogashira coupling, [Pd]-catalyzed nitroalkyne cycloisomerization leading to isatogens, and addition of indoles to isatogens using InCl3- and [Rh]-catalyzed oxidative N-heterocyclization of amino alcohol to form the key amide bond. In addition to these, the removal of the protecting groups has also been carried out in a selective fashion employing either catalytic or stoichiometric metal/metal-based reagents.

Metal-mediated alkynediol cycloisomerization: first and second generation formal total syntheses of didemniserinolipid B - Das, Shyamsundar; Induvadana, Boddeti; Ramana, C. V. (Tetrahedron, 2013)
A formal total synthesis of didemniserinolipid B was developed by employing a regioselective metal-mediated 6-endo-dig alkynol-cycloisomerization reaction. Two routes for the synthesis of key Burke's intermediate have been developed. Our initial approach involved the introduction of a C-17-allcynol followed by Pd-mediated cycloisomerization and then coupling with the serinol unit prior to the introduction of an alpha,beta-unsaturated ester unit through selective oxidation of 1 degrees-OH followed by a two-carbon Wittig homologation. Alternatively, the second generation strategy featuring the serinol coupling with the C-17-alkynol followed by alkyne addition to the epoxide and subsequent Au-mediated cycloisomerization of an acetonide protected alkynediol unit has been executed. This approach has avoided several late stage protection-deprotection events. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Alkynol-cycloisomerization; Bicyclic ketal; Gold catalysis; Palladium catalysis; Zipper reaction

Synthesis of Ag-glyconanoparticles using C-glycosides, their lectin binding studies and antibacterial activity - Ramtenki, Vilas; Raju, D.; Mehta, Urmil J.; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2013)
Two 12-C-glycosyl dodecanoic acids, namely, 1-(alpha-D-mannopyranosyl)-12-dodecanoic acid and 1-(alpha-D-glucopyranosyl)-12-dodecanoic acid were synthesized. Their ability to act as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles is displayed. These Ag C-glycosyl nanoparticles were later utilized to investigate the carbohydrate-lectin interactions. Furthermore, the specificity of mannoside binding to the surface of the Gram negative bacterium Escherichia coli has been utilized to demonstrate the enhanced antibacterial activity of Ag-C-mannosyl nanoparticles towards this bacterium as compared to Ag-C-glycosyl nanoparticles.

Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium

Polarization switching characteristics of 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) lead free ferroelectric thin films by pulsed laser deposition - Kolekar, Y. D.; Bhaumik, A.; Shaikh, P. A.; Ramana, C. V.; Ghosh, K. (JOURNAL OF APPLIED PHYSICS, 2014)
We report on the ferroelectricity for morphotropic-phase-boundary lead (Pb) free 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) (0.5BZT-0.5BCT) thin films. Thin films were grown on Pt/Ti/SiO2/Si substrate using pulsed laser deposition. Raman spectroscopic data combined with the X-ray diffraction analyses confirm body centered tetragonal crystallographic structure 0.5BZT-0.5 BCT thin films on Pt/Ti/SiO2/Si. Polarization studies demonstrate that these 0.5BZT-0.5BCT films exhibit a large remnant and saturation polarization of 37 mu C/cm(2) and 40 mu C/cm(2), respectively, with a coercive field of 140 kV/cm. A correlation between polarization dynamics, structural distortion, and phonon vibration is established. The splitting of X-ray diffraction peak of the thin film in the 2 theta range of 44.5 degrees to 46.5 degrees represents high degree of tetragonality. The tetragonality factor calculated by Rietveld analysis was found to be 0.006 and can be a major cause for the increased remnant polarization value. It is established from Raman spectra that the non-centrosymmetricity due to the displacement of Ti/Zr ions from its octahedral position is related to the peak position as well as the broadening of the A(1) (LO) optical phonon mode. This increase of broadness in the thin film causes an increase in the dipole moment of the unit cell and, hence, the net increase in polarization values. (C) 2014 AIP Publishing LLC.

Synthesis of the central tricyclic core of the isatisine A: harmonious orchestration of [metal]-catalyzed reactions in a sequence - Patel, Pitambar; Reddy, B. Narendraprasad; Ramana, C. V. (Tetrahedron, 2014)
Two sequential metal-catalyzed transformations, involving [In]-catalyzed Friedel Crafts type addition of spiroaminol carbon to indole C3 followed by [Rh]-catalyzed dehydrogenative cyclization of the resulting gamma-amino alcohol culminated in the construction of the central tricyclic core isatisine A. The overall strategy employed three easily available starting compounds and delivered the complex tricyclic core in four steps with all four steps being catalytic in nature. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Dehydrogenative cyclization; Friedel-Crafts reaction; Indium chloride; Isatisine A; Rhodium; Spiro-3-indolinone

Total synthesis of mangiferaelactone - Vadhadiya, Paresh M.; Ramana, C. V. (Tetrahedron Letters, 2014)
Herein we document the first total synthesis of mangiferaelactone and thus establish its absolute configuration. The central nonenolide ring was constructed using ring closing metathesis and Yamaguchi esterification. The key alcohol fragment was synthesized by the Bernet-Vasella fragmentation of C-ribofuranoside. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bernet-Vasella fragmentation; Nonenolide; Ring closing metathesis; Total synthesis; Yamaguchi protocol

Total synthesis of naturally occurring cephalosporolides E/F - Kona, Chandrababu Naidu; Ramana, C. V. (Tetrahedron, 2014)
A modular total synthesis of cephalosporolides E/F featuring sequential epoxide-alkyne coupling and subsequent highly regioselective gold catalyzed alkynolcycloisomerizatio of the resulting alkynetetrol to construct the central spiroketal core has been documented. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Alkynetetrol; Cephalosporolide; Epoxide-alkyne coupling; Gold catalysis; Spiroketalization

Pd-catalyzed benzylic C-H oxidation of cyclotriveratrylene - product diversity - Senthilkumar, B.; Gonnade, Rajesh G.; Ramana, C. V. (Organic & Biomolecular Chemistry, 2015)
The inner-rim functionalization of CTV has been examined by employing Pd-catalyzed benzylic oxidation. The outcome of the oxidation depends upon the solvent and co-oxidants employed. An interesting array of CTV derivatives has been synthesized with a simple change in the conditions.

Studies toward the total synthesis of cytospolide E - Vadhadiya, Paresh M.; Rout, Jeetendra K.; Ramana, C. V. (Tetrahedron, 2015)
In this manuscript, we describe various approaches that we have examined towards the total synthesis of Cytospolide E. We initially attempted the RCM approach employing first and second generation Grubbs and Grubbs-Hoyeda catalysts resulting in the exclusive synthesis of the Z-isomer of Cytospolide E. With the Furstner catalyst, the dimerization involving the less hindered olefin was the exclusive event. Alternative approach documented is a successful cross-metathesis leading to a seco-acid with the requisite E-configuration and undesired macrodiolide formation during the attempted Shiina's lactonization. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 20-Membered macrodiolide; Nonenolide; Ring closing metathesis; Shiina lactonization; Yamaguchi esterification

Studies toward the total synthesis of parvifolals A/B: an intramolecular o-quinone methide [4 + 2]-cycloaddition to construct the central tetracyclic core - Paymode, D. J.; Ramana, C. V. (ACS Omega, 2019)
Two different approaches funded upon the intramolecular [4 + 2]-cycloaddition of in situ generated o-quinone methides have been explored to construct the central tetracyclic core of parvifolals A/B. At the outset, a cross-pinacol coupling of 2-formyl tri-O-methyl resveratrol with 4-methoxysalicylaldehyde followed by acid treatment was found to provide the desired tetracyclic core with an internal olefin. The requisite pendant aryl group has been introduced by a Pd-catalyzed direct coupling of corresponding diazonium salt.